Brexit: As a Lesson and Challenge for ASEAN Integration or Vice Versa - Taufik, Abdullah Fathan; Jonni Mahroza; Surryanto D. W. (Technium Social Sciences Journal, 2020)
Over the last few decades, ASEAN is considered as a copycat of the system of the European Union (EU). ASEAN is considered weaker, lacks strong support from its members, has less substantive achievements, and is nothing more than competition between ASEAN member countries, where the EU has gone further in its implementation. This assessment has recently been canceled. The EU is currently faced with a list of daunting challenges - the ongoing debt crisis in Greece, increasing criticism by right-wing political groups over the European Union's fundamental agreement on freedom of movement within the EU. The refugee crisis and the growing movement of secession from member states - Britain and Spain are the most prominent examples. Of course, the EU now faces its most significant and most existent challenge, political vortex and divisions with the launch of a referendum in Britain, which resulted in 'Brexit.' This paper tries to analyze how Brexit phenomenon is suspected to occur in ASEAN due to the principle of regionalism, clashes with the sovereignty of each member country. The method used is descriptive analysis with a literature review. Based on research, Brexit in the EU has a context and substance of regionalism that is different from the conditions that exist in ASEAN. Nevertheless, Brexit is an early warning for ASEAN, which has heterogeneous regionalism. Furthermore, ASEAN is pushing for centrality and strengthening ASEAN integration in responding to the turmoil and political change taking place in the Southeast Asian region.